Assessment of human settlements and associated influential factors in Weihe River Plain. Issue 9 (November 2019) - Zhang, Yue; Hou, Kang; Chang, Yue; Li, Xuxiang; Yu, Chuck
As the main part of Guanzhong-Tianshui Economic Zone, involving the 44 areas in Weihe River Plain, we have conducted a quantitative analysis of the level of human settlements in this important region of China. The distribution of human settlement evaluation index (HSEI) was analysed by using the geographic information systems software and principal component analysis model to determine resources carrying capacity factors, natural environment factors and socio-economic factors. In order to better understand the level of human settlement, natural breaks classification method was adopted to divide results into five categories: unlivable (−0.35 to −0.10), low value livable (−0.10 to 0.04), livable (0.04–0.18), satisfactorily livable (0.18–0.41) and highly livable (0.41–0.99). Our results illustrate that the HSEI of areas, which have developed economy and tourism industry, is also high in HSEI in traditional industry and agriculture. Most regions are livable, satisfactorily livable and highly livable. The traditional impact of Weihe River on the quality of human settlement in this region is limited as the area has been moved on to modern development independent of the river.